Rambus friend or foe? [high-speed memory interface technology manufacture]. - Kumagai, J.
The author examines how Rambus' revolutionary technology and marketing savvy have put this small chip company on the map-and offended some of the biggest name in the business. The legal problems surrounding the high-speed memory interface technology manufacturer are also outlined
Keywords: DRAM; RDRAM; Rambus; SDRAM; Company; Dynamic RAM; High-speed memory interface technology manufacture; Legal problems; Marketing; Technology